2021
DOI: 10.13107/jocr.2021.v11.i05.2212
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Proximal Humerus Fracture with Anterior Shoulder Dislocation and Unilateral Chronic Bankart Lesion – A Case Report

Abstract: Introduction: Anterior shoulder dislocation is a common presentation in orthopedic emergency but a bilateral fracture dislocation is a rare entity. Only a few cases have been reported in the literature and their management is still not clear. We present a bilateral four part fracture dislocation with Bankart lesion on right side in a 48 years old. Case Report: A 48-year-old male presented with bilateral proximal humerus fracture with anterior shoulder dislocation following a seizure. He was managed with bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The authors concluded that coracoid osteotomy prevents re-dislocation and enhances the functional status of the shoulder joint [ 14 ]. Open reduction along with Latarjet is further supported by the case described by Anurag et al where they performed Latarjet for chronic bony Bankart in a 48-year-old lady with bilateral proximal humerus fracture and anterior dislocation following a seizure attack [ 15 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors concluded that coracoid osteotomy prevents re-dislocation and enhances the functional status of the shoulder joint [ 14 ]. Open reduction along with Latarjet is further supported by the case described by Anurag et al where they performed Latarjet for chronic bony Bankart in a 48-year-old lady with bilateral proximal humerus fracture and anterior dislocation following a seizure attack [ 15 ].…”
Section: Discussionmentioning
confidence: 95%
“…case described by Anurag et al where they performed Latarjet for chronic bony Bankart in a 48-year-old lady with bilateral proximal humerus fracture and anterior dislocation following a seizure attack [15].…”
Section: Discussionmentioning
confidence: 99%
“…From our analysis of the literature, the mean age of patients reported bilateral anterior dislocations was 32.5 years with standard deviation of 8.89 years (Table 1). The youngest patient was 20 years old [26] and the oldest was 48 years old [4] . All patients reported in the reviewed literature included our study were males which confirms the previous results of other studies showed predominance of men over female in having bilateral anterior dislocations [1,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral dislocations of the shoulder are one of the rarest medical conditions however, they arise on the joint the most subject to dislocations [1][2][3] . Moreover, this condition is most of the time presented as post-traumatic or secondary to convulsive seizures [2,4] . Anterior dislocation is rarer that posterior dislocation and few cases with anterior dislocations are reported in the literature [3,4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation